Effect of Using Herbicide 10% Ethyl pyrazosulfuron on Growth of Rojolele Srinuk Variety (Oryza sativa L. Var. Rojolele Srinuk) in Langensari Village Subdistrict Tarogong Kaler - Dewi Hernawati; Yayan Sumekar; Nida Zihar Uzbani (Department of Crop Science, Faculty of Agriculture, Andalas University, 2024)
Weeds are nuisance plants that grow in unwanted areas and inhibit the growth of paddy rice cultivation, which can reduce the quantity of rice yield Therefore, weeds need to be controlled. This study aims to determine : 1) the effect of using 10% Ethyl pyrazosulfuron herbicide on the growth of Rojolele Srinuk variety of paddy rice (Oryza sativa L. var. Rojolele Srinuk) and 2) the correct dose of 10% Ethyl pyrazosulfuron herbicide for the growth of Rojolele Srinuk variety of paddy rice. This research was conducted in Langensari Village, Tarogong Kaler District. The research was conducted from November 2022 to February 2023. This study used a Randomized Group Design (RGD) with seven treatments and four repetitions, including 10% Ethyl pyrazosulfuron herbicide treatment at a dose of 150 g/ha (0.18 g/12 m2 ), 225 g/ha (0.27 g/12 m2 ), 300 g/ha (0.36 g/12 m2 ), 375 g/ha (0.45 g/12 m2 ), 450 g/ha (0.54 g/12 m2 ), manual weeding and control. The results showed that the use of 10% Ethyl pyrazosulfuron herbicide at a dose of 150 g/ha (0.18 g/12 m2 ) - 450 g/ha (0.54 g/12 m2 ) did not cause phytotoxicity or symptoms of poisoning to Rojolele Srinuk variety of paddy rice plants. Then, the use of the herbicide Ethyl pyrazosulfuron 10% affects the number of tillers of rice paddy varieties Rojolele Srinuk. The most effective dose of 10% Ethyl pyrazosulfuron herbicide in the growth of Rojolele Srinuk rice paddy is a dose of 450 g/ha (0.54 g/12 m2 ).